Exosomal communication: a pivotal regulator of bone homeostasis and a potential therapeutic target - Ye, Qian-Yun; Cui, Yan; Wang, Hao-Yu; Li, Ling-Yu; Chen, Jian-Bing; Zhu, Xiao-Feng; Xue, Zhi-Jian; Zhang, Rong-Hua (Frontiers in Pharmacology, 2024)
Bone homeostasis encompasses two interrelated aspects: bone remodeling and cartilage metabolism. Disruption of bone homeostasis can lead to the development of metabolic bone diseases such as osteoporosis and osteoarthritis. The maintenance of bone homeostasis is a complex process that does not solely rely on the functions of the bone tissue itself. In fact, bone tissue is not an isolated entity; it is closely connected to other tissues in the body via exosomes. Within this interconnectivity, exosomes derived from both bone and non-bone cells interfere with each other, forming a complex regulatory network. Therefore, with cell origin as the guiding principle, we have delineated the bone regulatory network of exosomes, elaborated on the specific roles and regulatory mechanisms of exosomes derived from common cell types (cells within the skeletal microenvironment, stem cells from extra-osseous tissues, vascular-derived cells, muscle-derived cells, and neurogenic cells) in bone formation, bone resorption, and cartilage metabolism. We have also discussed the challenges faced in the field of exosome research related to bone homeostasis, unveiled the critical role of exosomes in maintaining bone homeostasis, and proposed that exosomes could serve as highly valuable therapeutic targets for metabolic bone diseases.